IDENTIFICATION OF INFORMATION SHARING IN SUPPLY CHAIN MANAGEMENT (CASE OF WOVEN BAMBOO CRAFTS IN TOMOHON CITY) - Sengka, Ryan Reynaldo; Taroreh, Rita N.; Palandeng, Indrie Debbie (FEB Universitas Sam Ratulangi Manado, 2015)
One method of the application of Supply Chain Management is Information Sharing, where the level or quantity of information sharing is the level at which information is important and confidential in the company (proprietary) to be communicated to business partners in the supply chain. This shared information can vary, ranging from strategic information to the tactical information or information about events logistics, to information about markets and consumers. Through the use of available data and by sharing them with other parties in the supply chain, information can be used to build competitiveness. The aim of this research is to identify the Information Sharing at the Woven Bamboo Crafts in Tomohon. The method used is descriptive Qualitative Analysis that describes or explains aspects of the flow of information or how to share the information from all parties involved in the company. It can be concluded that parties who are associated are bamboo farmers, artisans / vendors and customers, and the way information is shared between the parties involved in the Woven Bamboo Crafts in Tomohon is through telephone or face-to-face (direct communication). The management of Woven Bamboo Crafts should use an e-commerce marketing-based system that uses the internet to market products of woven bamboo so that more people will know the existence of the product. Keywords: information sharing, supply chain management